Drug utilization review of anticancer drugs in cancer outpatient department of the Government Medical College, Aurangabad - Kulkarni, M. D.; Hussaini, Samra A.; Padwal, S. L.; Khandelwal, P. N.; Doifode, S. M.; More, P. P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study drug utilization of anticancer drugs in cancer outpatient department (OPD) of Government Medical College, Aurangabad. Methods: Five hundred and twelve prescription records were screened and analyzed as per the study parameters from cancer OPD of Government Medical College and Hospital, Aurangabad. Commonly used anticancer drugs were recorded; furthermore, different types of carcinomas were noted. Results: Age group of patients was in between 30 and 70, 267 were females and 245 were male patients. The most common type of carcinoma was carcinoma of the breast (17.9%). Carboplatin was the most commonly used anticancer drug (26.56%). The average number of anticancer drugs received per patient was three. Conclusion: WHO suggested drug utilization studies are needed in every health care setting. For a developing country like India, National Drug Policy and Drugs and Therapeutic Committee are a must.